The Influence of Green Human Resource Mangement Mechanisms on Sustainable Business Outcomes in Customer-Centric Digital Enterprises - Muchsinati, Evi Silvana; Lina, Lina; Fatyandri, Adi Neka (Journal of Social Commerce, 2025)
This study examines how Green Human Resource Management contributes to organizational sustainability performance by investigating the psychological mechanisms that shape this relationship. Using structural equation modeling on data collected from employees in environmentally engaged firms, the research explores the extent to which the influence of green HR practices is mediated by perceived organizational support and affective commitment. The findings suggest that GHRM does not operate in a vacuum. Its impact becomes significant when employees interpret these practices as authentic expressions of support and when they experience a sense of emotional connection to the organization’s mission. Perceived support functions as a cognitive filter through which green initiatives are assessed for credibility, while affective commitment emerges as a behavioral engine that channels belief into sustainable action. These results underscore that sustainability outcomes are shaped less by the presence of formal policies and more by the quality of interpretive and emotional engagement they evoke. The study offers not only empirical confirmation but also conceptual insight into the relational infrastructure needed for organizations to embed sustainability in practice, particularly within digitally driven and customer-centric environments.